Complete mitochondrial genomes of two damselfly species in coenagrionidae and phylogenetic implications. Issue 8 (3rd August 2021) - Jiang, Bin; Li, Jia; Zhang, Yongmei; Sun, Yang; He, Shulin; Yu, Guozhi; Lv, Guosheng; Mikolajewski, Dirk J.
Abstract: Agriocnemis femina (Brauer, 1868) and Ischnura senegalensis (Rambur, 1842) are two damselflies inhabiting paddy lands. As an intermediate predator, they play an important role in controlling certain crop pest and mosquitoes. In this study, we sequenced complete mitogenomes of these two species. The total length of mitogenomes is 15, 936 bp in A. femina and 15, 762 bp in I. senegalensis . Both of mitogenomes consist of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one control region. The close relationship between I. senegalensis and I. elegans was further proved by phylogenetic analysis. Our phylogenetic analysis indicated a clear two lineages in Coenagrionidae (Core and ridge-faced Coenagrionidae). Ridge-faced Coenagrionidae consisted of Megaloprepus caerulatus and Ceriagrion fallax . In core Coenagrionidae, Ischnura and Enallagma are most closely related; they formed one clade with Agriocnemis and then grouped together with Paracerion . Our study provides new genetic information for further study in phylogenetic analysis of Coenagrionidae.